Managerial Compensation and the Market Reaction to Bank Loans - Almazan, A. (Review of Financial Studies, 2003)
Journal Article Managerial Compensation and the Market Reaction to Bank Loans Get access Andres Almazan, Andres Almazan University of Texas Address correspondence to Andres Almazan, Department of Finance, McCombs School of Business, University of Texas at Austin, TX 78712-1179, or e-mail: andres.almazan@bus.utexas.edu. Search for other works by this author on: Oxford Academic Google Scholar Javier Suarez Javier Suarez CEMFI Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 16, Issue 1, January 2003, Pages 237–261, https://doi.org/10.1093/rfs/16.1.0237 Published: 16 June 2015